“Fecerat egregia constructum ex arte sepulcrum”: il monumento dantesco di Pietro Lombardo a Ravenna - Ceriana, Matteo (Opus Incertum, 2021)
The main purpose of the paper is to focus on the structure, the materials and the history of Dante’s memorial at San Francesco in Ravenna (1483). The marble and stone structure was produced by Pietro Lombardo and his workshop under commission from Bernardo Bembo, the Venetian politician and humanist who was podestà of Ravenna between 1482 and 1483. The memorial was probably dismantled in the 18th century when it was replaced in the new chapel designed by Camillo Morigia, yet it was rebuilt exactly as it was before, as we can conclude from the original project drawings (Paris, Bibliothéque Nationale) and from etchings of various later (18th century) reproductions. The Dante memorial focuses of course on the memory of the poet, but it is also part of a more extensive programme for the restoration of other monuments in Ravenna produced by Lombardo’s bottega, as well as of urban spaces that visually affirm the Venetian domination of the city at the time and under the Patrician government.